2008
DOI: 10.1007/s00464-008-0017-7
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of disruption in the operating room during laparoscopic antireflux surgery

Abstract: This study demonstrated the feasibility of using video-aided observational studies for developing objective assessment of team quality in the OR. Categorizing disruptive events and examining their negative impact on the OR time will help to develop methods to eliminate inefficiency inside the OR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 15 publications
7
59
0
Order By: Relevance
“…They are consistent with findings that information exchanges in the OR often take place in less than ideal conditions [7][8][9], thus potentially causing additional stress to the operating surgeon, which in turn impacts negatively on teamworking and team cohesion [10,11]. A novel aspect of the present study is the approach to addressing these problems that the physicians in our sample proposed: skills training and standardization, in the form of protocols that everyone is aware of and uses, as well as in the form of IT systems.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They are consistent with findings that information exchanges in the OR often take place in less than ideal conditions [7][8][9], thus potentially causing additional stress to the operating surgeon, which in turn impacts negatively on teamworking and team cohesion [10,11]. A novel aspect of the present study is the approach to addressing these problems that the physicians in our sample proposed: skills training and standardization, in the form of protocols that everyone is aware of and uses, as well as in the form of IT systems.…”
Section: Discussionsupporting
confidence: 89%
“…In general surgical cases (open and laparoscopic), typically lasting between 30 min and 4 h, OR personnel have been found to experience an average of 3-4 distractions in their communication [7]. Another study found that disruptive communications were the most frequent cause of distraction in laparoscopic antireflux surgery [8]. OR personnel are aware that their work is frequently disrupted, with particular impact on the communications among them [9][10][11].…”
mentioning
confidence: 99%
“…The findings of the two observers for these six procedures were compared, and the interobserver agreement was calculated (function incorporated in The Observer Ò XT 11.5 software). If satisfactory interobserver agreement would be achieved, the remaining procedures could be annotated by the two observers separately (randomly allocated and analyzed in a non-chronological random order) [5,23].…”
Section: Methodsmentioning
confidence: 99%
“…Studies describing surgical processes were generally based on live observation in the OR; video observation has only been used infrequently [6,8,22,23]. Nevertheless, video registration is deemed superior since it is not limited by the capacity of an observer, cause-and-effect relationships are better analyzable, and the Hawthorne effect (i.e., the awareness of being observed alters the way a person behaves) is minimized [6,7,24,25].…”
mentioning
confidence: 99%
“…Several tools and methodologies have been developed and applied in surgery to quantify interruptions in surgical procedures (Zheng et al 2008;Parker et al 2010;Sutton et al 2010;Blocker et al 2010). Parker et al (2010) developed a surgical flow disruption tool that categorizes disruption events into 1) technical factors, 2) environmental factors, 3) technology and instruments, 4) training and procedures, 5) teamwork, and 6) others.…”
Section: Introductionmentioning
confidence: 99%